Proximate Analysis of Biomass - Rajas, Neha; Korde, Sushant; Kate, Ishita; Kale, Sai; Jadhav , Vicky (International Journal of Membrane Science and Technology, 2023)
One of the sustainable and renewable energy sources that doesn't produce a lot of greenhouse gas emissions is biomass. Using biomass energy effectively will aid in addressing issues brought on by the use of fossil fuels. The biomass has only issue of low calorific value. For biomass as a fuel the calorific value plays a very crucial role. Five diverse biomass species, such as dried Sugarcane Bagasse, Rice Husk, Cotton Waste, Mango leaves and Coal are represented in this context. Agricultural leftovers, coal, and sugarcane bagasse have all been identified through proximate analysis. In this we calculated (moisture, volatile matter, fixed carbon, and ash contents). Next, a number of empirical equations with linear and nonlinear terms are used. This paper also tells about the thermogravimetric analysis method.